Implementation of 2013 Curriculum in PAI Learning Process at SMP Al Manar - Neliwati Neliwati; Wantri Anggraini Berampu; Anisa Fadillah; Widia Rahayu (Universitas Muhammadiyah Enrekang, 2022)
The 2013 curriculum has been implemented as the national curriculum since the 2013/2014 academic year, so knowing the implementation of the 2013 curriculum is very necessary because you can see the effectiveness of its implementation and know the learning process that has been implemented. The aims of this study were to 1) describe the implementation of the 2013 curriculum at YP AL MANAR 2) explain the views of school principals, those in charge of the curriculum, teachers and students regarding the implementation of the 2013 curriculum in the PAI learning process at YP AL MANAR. 3) Formulate what factors support and hinder the implementation of the 2013 curriculum in the PAI learning process. This research is a qualitative research using a phenomenological approach. Data collection techniques carried out by researchers using interviews, observation, and documentation. The research results obtained were that the Implementation of the 2013 Curriculum in PAI subjects in the PAI learning process was not optimal, there were obstacles or obstacles in the learning process and had supporters for the implementation of the 2013 curriculum. In detail it can be concluded as follows: (1) Implementation of the 2013 Curriculum in subjects PAI in the PAI learning process has been implemented but not optimal. (2) Obstacles to implementing the 2013 Curriculum in the PAI learning process are the difficulty of carrying out scientific learning because students are not active and lack confidence. (3) Supporting the implementation of the 2013 curriculum at YP Al MANAR can be seen through teacher training activities carried out in schools to form teachers to be able to carry out the learning process according to the 2013 curriculum. learning at YP Al MANAR effectively.